The Magnitude and Distance Decay of Trade in Goods and Services: New Evidence for European Countries - Martijn J. Burger; Mark Thissen; Frank G. van Oort; Dario Diodato (Tinbergen Institute, 2014)
Using a newly assembled, consistent and disaggregated dataset (12 goods and 7 services) on internal and bilateral trade for 25 European countries, we analyse the difference between trade in goods and services. The measurement of both trade in goods and trade in services is improved over earlier research, allowing us to compare trade in goods and services in a coherent and systematic way. First, our dataset is made consistent with the domestic demand and production and the total exports and imports at the sector and product level. Second, we explicitly control for re-exports. We find that, although goods are more often bilaterally traded than services, the volume of bilateral trade in services does not attenuate less with distance than the volume of bilateral trade in goods.
Keywords: F10; F14; 330; services; goods; trade costs; Europe